Das patristische Prinzip : eine Studie zur theologischen Bedeutung der Kirchenväter - Merkt, Andreas. (Vigiliae Christianae, Supplements, 2001)
The patristic principle demands that theological quarrels be settled by resorting to the church fathers. This volume presents the first comprehensive reflexion on the historical evolution of the present crisis of this ancient theological principle. Focusing on the theory of the consensus quinquesaecularis , the author surveys the development of patristic authority from the 16th to the 20th centuries and relates it to other problems of the Church in modern times such as the crisis of tradition, the conflict between ecclesiastical authority and academic theology, and ecumenism. The concluding chapter tackles the question whether a renewal of the patristic principle is possible and feasible today.